Analisis Prinsip Ekowisata di Pantai Sejile Labuhan Merak Taman Nasional Baluran - Devian Putri Monikasari; Ayu Wanda Febrian; Randhi Nanang Darmawan (Yayasan Literasi Sains Indonesia, 2023)
Sejile Beach is one of the beaches in the Baluran National Park area located in Sumberwaru Village, Banyuputih District, Situbondo Regency. This beach is know as Sejile because it has the potential and tourist attraction to be transformed into ecotourism by taking into account the existing problems. The aim of the research is to anlyze the principles of conservation and tourism with possible risks that occur through the AS/NZS 4360 in 2004 Risk Management approach, which is beneficial for managers and the community in managing tourism objects. This study uses a qualitative descriptive method with a risk management approach AS/NZS 4360, 2004, while the stages are: determining the risk context, risk analysis, evaluation, and risk control, for data collection techniques namely observation, interviews, literature studies, and documentation. This research is expected as a recommendation to the management and the community to consider frameworks or programs that have been built or are still in the planning stages at tourist sites, with possible risks that occur, both environmental and human factors, in order to make conservation tourism sustainable.